(untitled) (The Research of Medical Science Review, 2025)
Spinach is rich in antioxidants as it is good provider of iron and folic acid, but these vegetables are spoiled by these chemicals and become toxic. The experiment was conducted at the research area of Botanic Garden, Government College University Faisalabad, Pakistan to examine the effect of foliar application of selenium and zinc on spinach (Spinacia oleracea L.) under salt stress. Seeds of spinach variety “Desi palak”. Salinity 100 mM NaCl was applied after one week of germination. Sodium selenate was used as a source of selenium applied foliarly at 0.01%, 0.02 %, 0.03% Se with three replications under normal and saline conditions. Zinc sulphate was used as a source of zinc and was applied foliarly at 0.10%, 0.20%, 0.30% Zn with three replications under normal and saline conditions. Biochemical attributes were determined at seedling stage. The data collected was analyzed statistically by CoStat software. The data collected from the experiment shows that salinity reduces the physiological attributes like plant height, shoot and root length, shoot and root fresh & dry weight, number of leaves and leaf area.